What drives bilateral remittances to Pakistan? A gravity model approach - Junaid Ahmed; Inmaculada Martinez-Zarzoso (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
Formal remittance flows to Pakistan have shown noticeable growth over the past decade. Using bilateral remittance data for 23 major source countries, this study examines the external and internal factors driving these remittance flows during the period 2001-2011. We estimate a gravity model for bilateral remittance flows using a variety of panel data techniques suitable to control for unobserved heterogeneity as well as simultaneous bias existing between remittances and migrant's stock. The main novelty with respect to the existing literature is the use of transaction costs of remittances as a superior alternative to geographical distance to proxy for remittance costs. We find that several factors have a significant effect on remittances, such as improved economic conditions in the receiving country, Pakistani migrant's stock in the source country, and financial development and political stability in the recipient country. Geographical distance, economic conditions and the unemployment rate in the source countries, however, do not appear to play a substantial role. We also find that geographical distance seems to be a poor proxy for the cost of remitting. This can be better understood in terms of migrant networks and improvements in receiving and source country financial services. While the effect of transaction costs of remittances' on remittance flows is found to be negative, its significance is not robust to changes in the specification of the estimated models.
Keywords: F22; F30; J61; O11; O24; 330; remittances; gravity model; stock of migrant; geographical distance; transaction cost; financial development; political stability; Pakistan